Influence of anthropometric characteristics on speed abilities of 14 years old elite male basketball players - Jakovlevic, S.; Karalejic, M.; Pajic, Z.; Gardasevic, B.; Mandic, R. (Journal of Physical Education and Sport, 2011)
The aims of this study were: a) to identify anthropometric characteristics and speed abilities of 14 year old elite male basketball players b) to investigate relations between these two qualities. At the sample of total of 50 young basketball players, 14 years old, 11 anthropometric (predictors) variables were measured: four longitudinal measures, two transversal measures, body mass, four circumferences, six skinfolds and 2 derived variables: body mass index (BMI), and sum of skinfolds (SUM SKF). Also, they did three speed tests (dependent variables): run 20m, run 30m, and run 50m. For the assessment of influence of predictor variables on dependent variables regressive analysis, Stepwise method, was applied. Results of three regression analysis talk about a moderate, but significant influence of anthropometric variables on results of 20m (first step - variable lower limb length), 30m (first step - variable sitting height and second step - variable sum of skinfolds) and 50m (first step - variable sum of skinfolds) sprint tests of 14 years old basketball players.